Role of resveratrol in inhibiting pathological cardiac remodeling - Fan, Shaowei; Hu, Yuanhui; You, Yaping; Xue, Wenjing; Chai, Ruoning; Zhang, Xuesong; Shou, Xintian; Shi, Jingjing (Frontiers in Pharmacology, 2022)
Cardiovascular disease is a group of diseases with high mortality in clinic, including hypertension, coronary heart disease, cardiomyopathy, heart valve disease, heart failure, to name a few. In the development of cardiovascular diseases, pathological cardiac remodeling is the most common cardiac pathological change, which often becomes a domino to accelerate the deterioration of the disease. Therefore, inhibiting pathological cardiac remodeling may delay the occurrence and development of cardiovascular diseases and provide patients with greater long-term benefits. Resveratrol is a non-flavonoid polyphenol compound. It mainly exists in grapes, berries, peanuts and red wine, and has cardiovascular protective effects, such as anti-oxidation, inhibiting inflammatory reaction, antithrombotic, dilating blood vessels, inhibiting apoptosis and delaying atherosclerosis. At present, the research of resveratrol has made rich progress. This review aims to summarize the possible mechanism of resveratrol against pathological cardiac remodeling, in order to provide some help for the in-depth exploration of the mechanism of inhibiting pathological cardiac remodeling and the development and research of drug targets.